Effectiveness and use of evidence-based cardiovascular preventive therapies in type 2 diabetes patients with established or high risk of atherosclerotic cardiovascular disease - Tian, Jian-Qing; Zhang, Zhi-Jun; Peng, Yi-Ting; Ye, Jia-Wen; Wang, Zhi-Yi; Lin, Yu-Hao (Frontiers in Endocrinology, 2025)
AimTo explore the association of evidence-based cardiovascular preventive therapies with cardiovascular and renal outcomes in type 2 diabetes (T2DM) patients with established or high risk of atherosclerotic cardiovascular disease (ASCVD).MethodsIn this cohort study, we identified T2DM patients with established or high risk of ASCVD using diagnostic codes from the institutional data of Xiamen Humanity Hospital between 2018 and 2023. Cohort 1 includes participants who were visited between 2018 and 2020, with follow-up until occurrence of an endpoint or December 31, 2020. Participants who were visited between 2018 and 2023 were included in cohort 2. A total of 5,335 patients were included in cohort 1, and 17,320 patients were included in cohort 2. Primary outcomes were hazard ratios (HRs) for the composite of 3-point major adverse cardiovascular event (3-P MACE), hospitalization for heart failure (HHF), and end-stage kidney disease or doubling of serum creatinine level.ResultsRelative to patients’ non-use of evidence-based cardiovascular preventive therapies, the use of at least one evidence-based cardiovascular preventive therapy was associated with a lower risk of the 3-P MACE (HR, 0.82; 95% confidence interval [CI], 0.67 to 0.98), HHF (HR, 0.66; 95% CI, 0.47 to 0.92) and end-stage kidney disease or doubling of the serum creatinine level (HR, 0.73; 95% CI, 0.60 to 0.89) after adjustment for potential confounders. From 2018 to 2023, the use of glucagon-like peptide 1 receptor agonists increased from 2.7% to 13.7%; sodium–glucose cotransporter 2 inhibitors increased from 3.9% to 16.5%; angiotensin-converting enzyme inhibitors/angiotensin-II receptor blockers increased from 28.1% to 43.0%; moderate-intensity statins increased from 61.6% to 70.5%; and aspirin increased from 23.7% to 32.9%.ConclusionsThis study demonstrated that T2DM patients with established or high risk of ASCVD might benefit from the use of evidence-based cardiovascular preventive medications with respect to the risk of 3-P MACE, HHF, and end-stage kidney disease or doubling of the serum creatinine level. Despite a modest annual increase in the use of evidence-based cardiovascular preventive medications in T2DM individuals with established or high risk of ASCVD, multiple strategies are needed to overcome barriers to the implementation of evidence-based therapies.